Interpretation of "Wala Taqtulu" & "Faqtulu" and Their Relevance to Suicide from Maqasidi's Perspective - Siti Nur Ismah (Indonesian Journal of Innovation Multidisipliner Research, 2024)
This research examines the interpretation of the concept of suicide in QS al-Baqārah 54 and al-Nisā 29-30. Using the method approach of Tafsir Maqāṣidi Abdul Mustaqim and is a type of qualitative research with descriptive analysis. Through this research, there are several results that the practice of suicide once occurred among the people of the Prophet Moses as atonement for sins {2}:54 and Allah actually forbade the practice of suicide in {4}:29-30. If we look closely, many interpreters say that in the current context, suicide in the Qur'an is more suited to killing one's desires, and cannot be interpreted as suicide literally, because there is a prohibition on the practice of suicide as stated in {4}:29-30. Maqasidi from both verses contains elements of hifz al-Nafs, by not being able to protect the soul, resulting in no continuity of descent which is contrary to hifz al-nasl and in the absence of continuity of descent it is the same as the cessation of Islamic preaching which should be carried out by mankind so in this kills him the same as destroying hifz al-din.